Sequentially rotated loop and spiral antenna arrays with a coplanar C‐figured feedline - Hirose, Kazuhide; Tsubouchi, Susumu; Ito, Naonoshin; Urushibata, Yuya; Nakano, Hisamatsu (Electronics letters, 2023)
Using the moment method, two array antennas are investigated to reveal the effects of different radiation elements on the array characteristics. Each array comprises four elements sequentially rotated by 90° and excited by a coplanar C‐figured feedline above the ground plane. It is found that a loop element array has a 3 dB axial ratio bandwidth of 30%, 3.3 times as wide as that of an isolated loop without an array environment. In contrast, a spiral element array shows a 3 dB gain drop bandwidth of 62% (72% for the axial ratio bandwidth, wider than that of an isolated spiral by a factor of 3.0). Almost the same factors of 3.0 and 3.3 for the spiral and loop element arrays are then compared with those in similar studies. It is found that factors are classified into three groups by feedline types. The simulated results are verified by experimental work. Using the moment method, two array antennas are investigated to reveal the effects of different radiation elements on the array characteristics. Each array comprises four elements sequentially rotated by 90° and excited by a coplanar C‐figured feedline above the ground plane.